2018
DOI: 10.1177/1933719117728800
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Stimulation in Patients With Cancer: Impact of Letrozole and BRCA Mutations on Fertility Preservation Cycle Outcomes

Abstract: In women with cancer undergoing FP, letrozole appears to enhance response to ovarian stimulation while the presence of BRCA mutations is associated with lower oocyte and embryo yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 45 publications
(62 reference statements)
1
44
0
Order By: Relevance
“…A prospective study by Turan [20] also confirmed that BRCA1 had lower oocyte yield compared to BRCA negative and untested patients, also reporting the same findings for BRCA2 mutated patients.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…A prospective study by Turan [20] also confirmed that BRCA1 had lower oocyte yield compared to BRCA negative and untested patients, also reporting the same findings for BRCA2 mutated patients.…”
Section: Discussionmentioning
confidence: 57%
“…It would be of particular interest to assess which is the relevance of these oncologic events as confounding factors in BRCA1/2 women reduced fertility. [13,[15][16][17] The previous six studies related to this topic, addressing ovarian stimulation in BRCA 1/2 subjects, did not analyze in detail the potential role of oncologic history itself, independent of BRCA mutations, as fertility performance determinant [16,[18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Although interruption of adjuvant endocrine therapy is used in daily practice, its safety is still under investigation in the POSITIVE trial (ClinicalTrials.gov Identifier: NCT02308085) [33]. For patients with BRCA 1/2-gene mutations, another argument for embryo or oocyte cryopreservation can be the option of PGD and the possibly shorter reproductive life span in these patients [34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Cancer patients were younger (32.3 AE 3.5 vs. 37.2 AE 4.9 years) and obtained a significantly higher number of vitrified MII oocytes per cycle (8.7 AE 6.9 vs. 7.3 AE 5.6). As shown in the prior study, a significant lower number of cancer patients returned to the fertility clinic for trying to attempt pregnancy ( [28,29].…”
Section: Fertility and Cancer In Young Adult Womenmentioning
confidence: 76%